Development and characterization of liposomal formulation of bortezomib - Deshantri, Anil K. (Int J Pharm X, 2019)
Bortezomib is a proteasome inhibitor used for the treatment of multiple myeloma. The poor pharmacokinetic profile and off-target adverse effects provide a strong incentive to develop drug delivery systems for bortezomib. In the past, liposomal encapsulation has been proven to improve the therapeutic index of a variety of anti-neoplastic therapeutics. Here, we developed and characterized liposomal bortezomib formulations in order to find the most optimal loading conditions. Polyols were used to entrap bortezomib inside the liposomes as boronate ester via a remote loading strategy. Effect of various polyols, incubation duration, temperature, and total lipid concentration on loading efficiency was examined. Moreover, the effect of drug/lipid ratio on the release kinetics was studied. Loading efficiency was maximal when using meglumine plus mannitol as entrapping agents. Loading at room temperature was better than at 60 °C and loading efficiency was increased with increasing total lipid concentrations. There was a positive correlation between drug/lipid ratio and released amount of bortezomib. In vitro release kinetics in HBS and human plasma showed time dependent release. In HBS, at 4 °C, only 20% of the drug was released in three weeks, whereas at 37 °C 85% of the drug was released in 24 h. In human plasma, 5% of the drug retained after 24 h indicating faster release. Taken together, the most favorable liposomal formulation of bortezomib should be further exploited to study in vitro and in vivo efficacy performance.